(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the creation and use of electronic software in teaching “Information and communication technologies in agriculture”. This article reveals the structure and use of the student’s personal account. Currently, based on the needs of the time, an important issue remains the training of students studying in the field of agriculture, using information and communication technologies. Although the method of creating and using electronic software is studied by scientists of various specialties, the improvement of electronic software for teaching “Information and communication technologies in agriculture” has not been studied as a separate subject. The model of the science of improving information technology in agriculture in the context of e-education is disclosed in accordance with the effectiveness of the educational process and its goals and objectives.